THE ROLE OF TECHNOLOGY IN REDUCING TAX EVASION IN INDIA - S M Seetalad; S K Patil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tax evasion remains a significant challenge in India, leading to substantial revenue losses and hindering economic development. However, the integration of technology into tax administration has played a crucial role in reducing tax evasion by enhancing transparency, improving compliance, and strengthening enforcement mechanisms. This paper explores the impact of technology on tax compliance in India, highlighting key digital initiatives such as the Goods and Services Tax Network (GSTN), e-filing systems, artificial intelligence (AI), big data analytics, blockchain, and automation. The implementation of GSTN has revolutionized indirect tax collection by automating invoice matching, introducing e-way bills for tracking goods movement, and ensuring seamless tax reporting. AI-driven analytics and big data processing enable tax authorities to detect fraudulent activities, such as false input tax credit claims and underreporting of income. The integration of Aadhaar and PAN has further enhanced transparency by linking financial transactions to a unified identification system. Moreover, Operation Clean Money (OCM), launched post-demonetization, effectively leveraged AI and data analytics to identify tax evaders by scrutinizing large cash deposits. Additionally, blockchain technology is being explored to prevent invoice fraud and ensure tamper-proof tax records. Automation in tax administration, including e-invoicing and real-time tax deduction mechanisms, has minimized human intervention and corruption, leading to higher compliance rates. These advancements have resulted in increased tax revenues, a broader taxpayer base, and reduced opportunities for fraud. Despite these successes, challenges such as cybersecurity risks, digital literacy gaps, and evolving evasion tactics persist. Continued investment in emerging technologies and stricter enforcement measures will be essential for further strengthening tax compliance. This study concludes that technology-driven tax administration has significantly curtailed tax evasion in India and will continue to play a transformative role in ensuring financial transparency and economic stability.